Performance and Selection of Mutant Black Rice with High Lignin - Handayani, Rizky; Nandariyah, Nandariyah; Parjanto, Parjanto; Riyatun, Riyatun; Sutarno, Sutarno (Universitas Panji Sakti, 2024)
Eating black rice can avoid the risk, reduce insulin in the body, bind free radicals, and reduce weight. However, black rice still has disadvantages, like long life, tall stems, less resistance to pests and diseases, and low yields. Activities were carried out from August 2023 to November 2023 in Pakahan Village, Jogonalan, Klaten. The planting materials used were selected M3 mutant black rice seeds irradiated with 200 Gy gamma rays and Cempo Ireng black rice as a control plant. Planting used a randomized complete block design without replication with the pedigree selection method. The parameters measured were harvest age, plant height, productive tillers, and seed weight per plant. Descriptive analysis was used and a 5% level T test was carried out to compare the characteristics of the M4 genotype with the control (without irradiation). The research results showed that 12 individuals containing high lignin were selected which could be further developed for the next generation.